Biofuel initiatives in West Africa and the Sahel: potential for success (2015)
Global warming has heightened the need to substitute fossil fuels with biomass-based energy sources. Some West African countries have recorded appreciable progress in this regard though with inadequate documentation. This study documents the extent of production and use of different biofuels and incentives for sustainability in the sub-region. Field visits were conducted in Benin, Ghana, Niger and Nigeria with the aid of structured questionnaire and focus group discussions; and literature search in Mali, Niger and Senegal to assess current scenarios. Biofuel crop production (jatropha, cassava and sugarcane) is on the rise, howbeit, with foreign investments. That cassava and sugarcane are important staples in the sub-region constitutes a possible hindrance to their adoption, arising from food crisis currently being experienced there. Jatropha appears the most appropriate potential species. There is the need for enabling policies to enhance the optimum production and utilization of Jatropha for biofuel production in the sub-region